2014
DOI: 10.1155/2014/843687
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-Based Cosmeceuticals

Abstract: Cosmeceuticals are the fastest growing segment of the personal care industry, and a number of topical cosmeceutical treatments for conditions such as photoaging, hyperpigmentation, wrinkles, and hair damage have come into widespread use. In the cosmeceutical arena nanotechnology has played an important role. Using new techniques to manipulate matter at an atomic or molecular level, they have been at the root of numerous innovations, opening up new perspectives for the future of cosmeceutical industry. Nanotech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
157
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(159 citation statements)
references
References 47 publications
0
157
0
2
Order By: Relevance
“…Therefore, it is no surprise that an estimated 83.1 billion dollars will be spent in the hair care market in 2016 [26]. Nanotechnology-based innovations are aimed at improving the stability of cosmetic ingredients, enhancing the aesthetic appearance of products and targeting active ingredients to the focal structures with controlled release and sustained effects [27]. Much research has focused on the ways in which nanomaterials can be used to improve hair cosmesis-maintaining shine, silkiness and health of hair.…”
Section: General Appearancementioning
confidence: 99%
“…Therefore, it is no surprise that an estimated 83.1 billion dollars will be spent in the hair care market in 2016 [26]. Nanotechnology-based innovations are aimed at improving the stability of cosmetic ingredients, enhancing the aesthetic appearance of products and targeting active ingredients to the focal structures with controlled release and sustained effects [27]. Much research has focused on the ways in which nanomaterials can be used to improve hair cosmesis-maintaining shine, silkiness and health of hair.…”
Section: General Appearancementioning
confidence: 99%
“…[1][2][3] A forecasted report suggested that by 2018, the global market for cosmeceuticals will reach ~42 billion dollars and lead to a great demand in near future. 4 Even though various synthetic compounds are currently available in the world market, human toxicity is increasing with cosmeceutical interference in certain treatments. [5][6][7][8] Alternatively, plant-derived natural, bioactive compounds show enhanced beauty roles, along with health benefits against diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The Kingdom's large and buoyant economy has been a key growth market and potential investment focus for cosmetics companies and global brands retailers shops (L'Oreal, Bath & Body Works, Boots, Marks & Spencer, Clara, Halal cosmetics market include Inika, One Pure, LLC, FX, etc…) [3,5,6]. Moreover, the competitive landscape featuring amongst the major cosmetics industries analysis has been conducted on the key strategies to support their clients' optimal understanding and source of knowledge related to the cosmeceuticals market worldwide [5][6][7]. It is worth noting that cosmetics are defined as care/make-up substance used to enhance the appearance or odor of the human body, while esthetics deals with beauty and the beautiful.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that cosmetics are defined as care/make-up substance used to enhance the appearance or odor of the human body, while esthetics deals with beauty and the beautiful. The industry covers different components including anti-ageing, growth factors, surgery and orthodontics, skin care, hair care, injectable and others esthetics products and services [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation